1991
DOI: 10.1021/bi00215a012
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-selective amphotericin B channels are predominant in vesicles regardless of sidedness

Abstract: Amphotericin B (AmB) is a membrane-active antibiotic which has been shown to increase ion and small molecule permeability in a variety of model and biological membrane systems. A major mechanistic model, based on BLM systems, proposes that amphotericin forms barrellike pores with cholesterol which are cation selective when added to one side of the membrane and anion selective when added to both sides. We have tested this hypothesis on small and reverse-phase large unilamellar vesicles (SUV and REV) with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 28 publications
4
56
0
Order By: Relevance
“…Stimulation of Ca 2ϩ influx is a possible mechanism and has been observed in human monocytes (18). However, it is unclear whether Ca 2ϩ is directly transported since the AMB-induced channels in cholesterol-containing model membranes are not appreciably Ca 2ϩ permeant (10,16). Alternatively, monovalent cation permeation could lead to membrane polarization or depolarization, leading to a secondary release of Ca 2ϩ from internal stores or from stimulated outer membrane Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of Ca 2ϩ influx is a possible mechanism and has been observed in human monocytes (18). However, it is unclear whether Ca 2ϩ is directly transported since the AMB-induced channels in cholesterol-containing model membranes are not appreciably Ca 2ϩ permeant (10,16). Alternatively, monovalent cation permeation could lead to membrane polarization or depolarization, leading to a secondary release of Ca 2ϩ from internal stores or from stimulated outer membrane Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that AmB weakly interacts with DPPC molecules. Hartsel et al (5) proposed that the insertion of AmB toward the lipid bilayer brings the polar polyol region in direct contact with the lipid hydrocarbon, and thereby induces some of the local lipid head groups to "fold around" so as to interact with the polyol. Such an unfavorable juxtaposition between AmB and phospholipid appears to occur in monolayers, resulting in the occurrence of a defect in the monolayers.…”
Section: Spectroscopic Characteristics Of Amphotericin B In An Aqueoumentioning
confidence: 99%
“…It has been accepted that AmB forms barrel-like pores with cholesterol, thus inducing permeability changes in the membranes (3). However, there is evidence that AmB itself interacts with cholesterol-free lipid vesicles to promote and increase the permeability (4)(5)(6). In this manner, while many studies have been performed to characterize the pore formation by AmB, it has been difficult to obtain a definite answer because of the complicated interaction of the drug with itself, with sterol, and with lipid and aqueous environments.…”
mentioning
confidence: 99%
“…AmB exerts its selective toxicity by forming ion channel assemblies that permeabilize plasma membranes in a sterol-specific manner. [4][5][6][7][8][9][10][11][12][13] Besides sterols, interaction with phospholipids has recently been reported to be important for the bioactivity of AmB; [14][15][16][17][18] we have previously reported that phosphatidylcholine (PC) with short acyl chains markedly enhanced the membrane-permeabilizing activity of AmB even when added as a minor constituent, while the PC with long acyl chains reduced the potency. 19 These observations can be accounted for by the hydrophobic matching between AmB and the acyl chains.…”
Section: Introductionmentioning
confidence: 99%